Development of a novel liquid chromatography-tandem mass spectrometric method for aristolochic acids detection: Application in food and agricultural soil analyses. (15th August 2019) - Chan, Chi-Kong; Pavlović, Nikola M.; Chan, Wan
Highlights: Nephrotoxic aristolochic acids (AA) contaminated food and soil of Balkans. Chronic exposure to AA via AA-tainted food resulted in renal fibrosis and cancer. A new LC–MS/MS method was developed for analysis of AAs in food and soil samples. Zn/H + treatment dramatically increase analytical sensitivity of AA in LC–MS/MS. The method detects for the first time AA in supermarket flour samples in Balkan area. Abstract: Prolonged dietary exposure to AA-contaminated food crops cultivated in contaminated farmland was shown to be one of the main culprits of Balkan endemic nephropathy. Ultra-sensitive methods for the detection of AA at trace levels are important for surveillance purposes. We report the development of a novel liquid chromatography-tandem mass spectrometry (LC–MS/MS) method for AA-detection. One striking feature of the method is that the Zn/H + -induced nitroreduction convert AA into their respective aristolactams, which dramatically enhances their analytical sensitivity. The method was applied to quantitate AA in food grains and soil samples collected from farming villages of Serbia, and flour samples purchased from supermarkets. To the best of our knowledge, this is the first report of detecting AA in food ingredients available in supermarkets, which is alarming because it reveals AA poses insidious threats not only to residents of rural farming villages, but also to people residing in urban areas.